Aortic valve surgery morbidity and mortality. - Francisco Bacallao San Julián; Irma Matos Santos; José Ramón Llanes Echeverría; Luis Guevara González; Rigoberto Chil Díaz; Armando Martin Martínez (ECIMED, 2012)
Introduction Cardiac valve replacement surgery substantially improved outcomes in patients with severe valvulopathies. Epidemiological studiesmake it possible to carry out the situation diagnosis, to identify and to hierarchize problems; as well as to take necessary and rational actionstowards modifying them.Objective The aim of this study is to characterize morbidity and mortality in the postoperative phase of aortic valve surgery at the HermanosAmeijeiras clinical and surgical hospital.Method A descriptive, retrospective and cross-sectional statistical analysis was carried out.Results Aortic stenosis was the disease with the highest number of patients (47). Non-combined aortic valve replacement was carried out on 54patients being 66.7% of the total number of patients. This is followed, in order of frequency, by the combination with mitral valve replacementthat was carried out on 17 patients (21%). 8 patients (9.9%) were revascularized at the same time aortic valve replacementwas carried out. 19mm and 21mm diameter mechanical prosthesis were used. The most frequent postoperative complications were arrhythmias,followed by low cardiac output and respiratory infections. Combined surgical operations had negative influences on morbidityand mortality.